WOMEN AND POLITICS: STUDY OF POLITICAL COMMUNICATIO OF WOMEN HEAD OF REGION - Sa’diyah El Adawiyah; Aida Vitayala; Titi Sumarti; Djoko Susanto (Universitas Muhammadiyah Semarang, 2018)
The low participation of women in politics leads to a lack of women's involvement in politics. Although there is already 30% quota of women's representation in politics, there are still not represented women's voices in politics, especially regional leader. One way to increase women'srepresentation is through political communication strategies involving women, affirmative action, women leadership and political education for women. Strategies carried out through messages and medias used. Give woman opportunities to empower other woman. Hopefully Indonesian women can participate in the political frenzy. Not only as a sweetener but directly involved in practical politics.